1970
DOI: 10.1136/adc.45.243.624
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Ventilation in the Respiratory Distress Syndrome: A Controlled Trial

Abstract: (1970). Archives

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

1970
1970
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 21 publications
1
17
0
Order By: Relevance
“…Reid et al (1967) showed a significantly lower mortality among ventilated infants 1000-2000 g compared with controls, though numbers particularly of very low birthweight infants (<1500 g), were small. Murdock et al (1970) on the other hand were only able to show such benefit for infants over 2000 g. Since these early studies were published refinements in ventilator technique have been made (Reynolds, 1975), means of ventilation which can sometimes avoid endotracheal intubation such as the use of a tightly fitting face mask, or a negative pressure respirator have been devised, and continuous positive airway pressure (Gregory et al, 1971) has been introduced. The latter may reduce the need for mechanical ventilation both in hyaline membrane disease and in recurrent apnoea.…”
Section: Discussionmentioning
confidence: 99%
“…Reid et al (1967) showed a significantly lower mortality among ventilated infants 1000-2000 g compared with controls, though numbers particularly of very low birthweight infants (<1500 g), were small. Murdock et al (1970) on the other hand were only able to show such benefit for infants over 2000 g. Since these early studies were published refinements in ventilator technique have been made (Reynolds, 1975), means of ventilation which can sometimes avoid endotracheal intubation such as the use of a tightly fitting face mask, or a negative pressure respirator have been devised, and continuous positive airway pressure (Gregory et al, 1971) has been introduced. The latter may reduce the need for mechanical ventilation both in hyaline membrane disease and in recurrent apnoea.…”
Section: Discussionmentioning
confidence: 99%
“…A few years later, CPAP was found to reduce minute ventilation and improve oxygenation in neonates with RDS (32)(33)(34)(35)(36)(37). While Ashbaugh and colleagues (31) attributed the beneficial effect of PEEP to its ability to reopen or recruit atelectatic alveoli and prevent alveolar collapse at end-exhalation (problems that they related to abnormalities in surfactant, see below), others have suggested that the decrease in cardiac output produced by PEEP is responsible for both the reduction in shunt and the increase in high V A /Q regions and dead space that occurs.…”
Section: Effects Of Peepmentioning
confidence: 99%
“…In 1967, Reid et al [17] reported that more infants with respiratory distress syndrome (RDS) survived if they were randomised to IPPV than to 'a modified Usher regimen' (O 2 and IV NaHCO 3 and glucose) between 3 and 6 h of age (8/10 survivors compared to 2/10). In 1970, Murdock et al [18] reported the results of a randomised comparison of ventilation with various different machines (including a negative pressure ventilator) and supplemental ambient O 2 for 221 outborn infants with RDS. Survival increased significantly amongst ventilated infants 6 33 weeks' gestation (36/92 vs. 6/26); no difference was seen amongst less mature infants.…”
Section: Respiratory Support For Extremely Preterm/elbw Infantsmentioning
confidence: 99%